The Study of Phisical Changes in Bireuen Pendopo (Case Study: Pre-Independence, Independence And After Area Expansion) - Cut Azmah Fithri; Mohammad S Arar; Shofia Farhan; Yenny Novianti (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Bireuen Regency is an area that has historical buildings from the Dutch colonial era, one of which is the Bireuen Pendopo. It is a cultural heritage building that is more than 70 years old based on the photo archive of Ir. Sukarno with the Bireuen fighter in 1948 and was certified as